2003
DOI: 10.1128/jb.185.1.142-147.2003
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Mycobacteria on Carbon Monoxide and Methanol

Abstract: Carboxydobacteria are a group of bacteria which are able to grow chemolithotrophically on carbon monoxide (CO) as the sole carbon and energy source under aerobic conditions (22,30 Microbiol. 1965Microbiol. , abstr. P108, 1965, and Actinoplanes, Microbispora, and Mycobacterium (4), have also been described.The facultatively chemolithotrophic bacterium Mycobacterium sp. strain JC1 (originally Acinetobacter sp. strain JC1 DSM 3803; reclassified by Song et al. [41]), is capable of growing aerobically not only on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
88
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(96 citation statements)
references
References 35 publications
7
88
1
Order By: Relevance
“…JC1 has no epitopes identical to those of the non-mycobacterial CO-DHs . Several mycobacterial species have been shown to consume CO (King, 2003;Park et al, 2003) and to have nucleotide sequences corresponding to a part of the large subunit of CO-DH (King, 2003). Phylogenetic analyses with a part of the deduced amino acid sequences of the tentative large subunit genes of CO-DHs in other mycobacteria have also suggested that mycobacterial CO-DHs form a subclade distinct from other CO-DHs in other bacteria (King, 2003).…”
Section: Characteristics Of the Cloned Gene Clustermentioning
confidence: 94%
See 1 more Smart Citation
“…JC1 has no epitopes identical to those of the non-mycobacterial CO-DHs . Several mycobacterial species have been shown to consume CO (King, 2003;Park et al, 2003) and to have nucleotide sequences corresponding to a part of the large subunit of CO-DH (King, 2003). Phylogenetic analyses with a part of the deduced amino acid sequences of the tentative large subunit genes of CO-DHs in other mycobacteria have also suggested that mycobacterial CO-DHs form a subclade distinct from other CO-DHs in other bacteria (King, 2003).…”
Section: Characteristics Of the Cloned Gene Clustermentioning
confidence: 94%
“…CO-DH from the bacterium is similar in molecular mass, subunit structure, cofactor composition and other properties to the enzymes of Gram-negative carboxydobacteria (Gram-negative CO-DH), although not immunologically related to them . We have also shown that several mycobacterial species are capable of carboxydotrophic growth and possess CO-DH enzymes that share common antigenic epitopes (Park et al, 2003). In addition, we have recently demonstrated that the CO-DHs from several mycobacteria, including Mycobacterium sp.…”
Section: Introductionmentioning
confidence: 97%
“…Seven of these proteins were characterized: (i) proteins of 64, 55 and 27 kDa encoded by the mpdB, mpdC and orf1 genes, respectively, described in this study; (ii) proteins of 67, 63 and 11 kDa corresponding to DnaK and GroEL/ES molecular chaperones, respectively; and (iii) a protein of 50 kDa, which is the methanol : NDMA oxidoreductase detected in Mycobacterium gastri (Bystrykh et al, 1993) and several other mycobacteria (Park et al, 2003). This latter protein was detected in crude extracts of M. austroafricanum IFP 2012 after growth on HIBA and 2-propanol (François, 2002), suggesting its involvement in assimilation of 2-propanol, a putative intermediate of the MTBE metabolic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…strain JC1 grown with methanol did not exhibit activities of the classical PQQ-containing MDH in Gram-negative bacteria, the NAD-dependent PQQ-containing MDH and cytochrome c-dependent MDH of A. methanolica, the NADdependent MDH of methylotrophic Bacillus, or the NADdependent glutathionine-requiring MDH and methanol oxidase of methylotrophic yeasts (Anthony & Zatman, 1967;Arfman et al, 1989;Duine et al, 1984;Kato et al, 1975;Mehta, 1975;Tani et al, 1972). Instead, the bacterium exhibited MDO activity during growth on methanol (Park et al, 2003), suggesting that this bacterium may use MDO as a key enzyme for the oxidation of methanol. However, it has not been identified whether MDO is the enzyme necessary for Mycobacterium sp.…”
Section: Introductionmentioning
confidence: 99%
“…strain JC1 can grow on methanol as the sole source of carbon and energy (Cho et al, 1985;Ro et al, 1997b;Song et al, 2002). In previous experiments (Park et al, 2003;Ro et al, 1997a), Mycobacterium sp. strain JC1 grown with methanol did not exhibit activities of the classical PQQ-containing MDH in Gram-negative bacteria, the NAD-dependent PQQ-containing MDH and cytochrome c-dependent MDH of A. methanolica, the NADdependent MDH of methylotrophic Bacillus, or the NADdependent glutathionine-requiring MDH and methanol oxidase of methylotrophic yeasts (Anthony & Zatman, 1967;Arfman et al, 1989;Duine et al, 1984;Kato et al, 1975;Mehta, 1975;Tani et al, 1972).…”
Section: Introductionmentioning
confidence: 99%